Show-and-Tell: An Interface for Delivering Rich Feedback upon Creative Media Artefacts - Colin Dodds; Ahmed Kharrufa (Multimodal Technologies and Interaction, 2024)
In this paper, we explore an approach to feedback which could allow those learning creative digital media practices in remote and asynchronous environments to receive rich, multi-modal, and interactive feedback upon their creative artefacts. We propose the show-and-tell feedback interface which couples graphical user interface changes (the show) to a text-based explanations (the tell). We describe the rationale behind the design and offer a tentative set of design criteria. We report the implementation and deployment into a real-world educational setting using a prototype interface developed to allow either traditional text-only feedback or our proposed show-and tell feedback across four sessions. The prototype was used to provide formative feedback upon music students’ coursework resulting in a total of 103 pieces of feedback. Thematic analysis was used to analyse the data obtained through interviews and focus groups with both educators and students (i.e., feedback givers and receivers). Recipients considered show-and-tell feedback to possess greater clarity and detail in comparison with the single modality text-only feedback they are used to receiving. We also report interesting emergent issues around control and artistic vision, and we discuss how these issues could be mitigated in future iterations of the interface.